India’s political development and its impact on international relations - Rothermund, Dietmar (The impact of Asian powers on global developments, 2004)
India has stood the test of time as the world’s largest democracy. Governments have been formed after free elections both at the central and the state levels. The peaceful transfer of power has become a regular feature of the Indian political system. There have sometimes been sporadic outbreaks of violence during election campaigns, but these have always soon subsided. The stability of the system has also been proven by the fact that the military has never intervened in internal politics and has always remained under civilian control. But under the calm surface of democratic continuity there has been a great deal of political change. For a long time, the Congress Party ruled India as a “centre party”, supporting the state and being supported by it. This was the case at the centre as well as in the federal states. The majority voting system (“first past the post”) favoured the “centre party” due to triangular contests in which opposition parties of the right and the left neutralised each other. The Congress Party always relied on the large “minorities” — Muslims and Untouchables — that had no chance to establish viable parties of their own under this electoral system. If India had a system of proportional representation, this would be different. The minorities would have their own parties that would be coveted coalition partners. But under the prevailing electoral system the Congress Party was itself, so to speak, a “permanent coalition”. This also explains why this party was not prepared to enter into coalitions with other parties even when it lost elections and could have remained in power with the help of coalition partners.